Associations of different obesity phenotypes with chronic disease comorbidity among urban and rural residents of 40 - 69 years old in Yangzhong city: a cross-sectional survey - Xiang FENG; Zhaolai HUA; Qiuping SHI; Yao LIU; Jinyi ZHOU; Haiyuan TONG; Jinhua ZHU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the associations of different obesity phenotypes with chronic disease comorbidities among middle-aged and elderly residents in Yangzhong city for precise prevention and control of chronic disease comorbidy in the population. MethodsFace-to-face interview with a questionnaire developed by domestic researchers, physical examination and laboratory tests were conducted among 6 899 residents aged 40 - 69 years recruited with stratified multistage random cluster sample in urban and rural regions of Yangzhong city, Jiangsu province from November 2017 through June 2021. Multivariate ordered logistic regression model was applied to analyze the effect of different types of obesity on chronic disease comorbidity in the residents. ResultsOf 6 581 participants finally included in the analysis, 3 957 (60.1%) were identified as having chronic disease comorbidity; the proportions of body mass index (BMI in kg/m2) -based overweight (24.0 - 27.9) and obesity ( ≥ 28.0) were 40.7% and 12.1%; the proportions of central obesity based on waist circumference (WC, ≥ 90 cm for males and ≥ 85 cm for females), waist to hip ratio (WHR, ≥ 0.90 for males and ≥ 0.85 for females), and waist to height ratio (WHtR, ≥ 0.50) were 35.3%, 79.6%, and 63.7%; the proportions of mixed obesity indicated by BMI + WC, BMI + WHR, and BMI + WHtR were 10.5%, 11.4%, and 11.8%, respectively. After adjusting for gender, age, education, marital status, annual household income, residence region, smoking, alcohol consumption, vegetable intake, fruit intake, physical activity, daily sleep duration and family history of chronic diseases, the results of multivariate ordered logistic regression analysis showed that the participants with following different obesity phenotypes were at increased risk of chronic disease comorbidity: BMI-based overweight (odds ratio [OR] = 1.736, 95% confidence interval [95%CI]: 1.575 - 1.915), BMI-based obesity (OR = 2.325, 95%CI: 2.012 - 2.687), WC-based central obesity (OR = 1.773, 95%CI: 1.615 - 1.947), WHR-based central obesity (OR = 1.956, 95%CI: 1.739 - 2.200), WHtR-based central obesity (OR = 1.968, 95%CI: 1.788 - 2.166), BMI + WC-based mixed obesity (OR = 2.590, 95%CI: 2.221 - 3.021), BMI + WHR-based mixed obesity (OR = 3.488, 95%CI: 2.908 - 4.185), and BMI + WHtR-based mixed obesity (OR = 2.845, 95%CI: 2.438 - 3.321). ConclusionBMI-based obesity, WC-, WHR-, and WHtR-based central obesity, and mixed obesity are all risk factors for chronic disease comorbidity among urban and rural middle-aged and elderly residents in Yangzhong city and special attention should be paid to the residents with WC-based central obesity and mixed obesity in prevention and control of chronic disease comorbidity.